Consent Requirements for Testing Health Policies: An Intercontinental Comparison of Expert Opinions - Berner-Rodoreda, Astrid; McMahon-Rössle, Shannon A.; Eyal, Nir; Hossain, Puspita; Rabbani, Atonu; Barua, Mrittika; Sarker, Malabika; Metta, Emmy; Mmbaga, Elia; Leshabari, Melkizedeck; Wikler, Daniel; Bärnighausen, Till (Journal of empirical research on human research ethics, 2022)
Individual informed consent is a central requirement for clinical research on human subjects, yet whether and how consent requirements should apply to health policy experiments (HPEs) remains unclear. HPEs test and evaluate public health policies prior to implementation. We interviewed 58 health experts in Tanzania, Bangladesh and Germany on informed consent requirements for HPEs. Health experts across all countries favored a strong evidence base, prior information to the affected populations, and individual consent for 'risky' HPEs. Differences pertained to individual risk perception, how and when consent by group representatives should be obtained and whether HPEs could be treated as health policies. The study adds to representative consent options for HPEs, yet shows that more research is needed in this field ? particularly in the present Covid-19 pandemic which has highlighted the need for HPEs nationally and globally.
Gesehen am 20.03.2023